Soil and land characteristics of rubber (Hevea brasiliensis) growing tracts of Karnataka and their suitability for rubber cultivation - Dhanorkar B A; Ananathanarayana R; Naidu L G K (Journal of Plantation Crops, 2010)
Eight pedon locations representing different rubber growing tracts of Karnataka were selected to study variations in soil, climate and productivity of plantations (latex yield). These pedons were analysed to study their physical and chemical properties. Leaf nutrient status was also determined from same site. Rubber growing soils of Dakshina Kannada and Udupi district were grouped under order Ultisols and classified as Ustic Kandihumults, Rhodic Kandiustults and Typic Kandiustults. Soils from Kodagu district were grouped under order Inceptisols and classified as Oxic Dystrustepts. All the pedon sites studied are moderately acidic with pH ranging from 5.1 to 5.9. The organic carbon content varied from 3.7 to 24.8 g/kg-1. The surface layers in general recorded higher amount of organic carbon. The cation exchange capacity varied from 2.2 to 9.9 cmol (P+) kg-1. Exchangeable Ca, Mg, K and Na are very low and are present in the following order Ca > Mg > K > Na. Available nitrogen status was medium where as available phosphorous in general was low. Available potassium dominantly was low. Sulphur status was adequate to high. The leaves of rubber plantations were low in N and K. P content was low to medium in range. Magnesium and calcium content was medium to high. Micronutrients like Fe, Cu, Mn, and Zn were adequate.
Keywords: Dry period; Foliar analysis; Land qualities; Land suitability; Soil classification